Evaluation of fermented plant extracts and wax degrading bacteria ON Phenacoccus solenopsis Tinsley of Hibiscus sp. - Ahmmed, Sultan (2023)
The mealybugs collected from hibiscus plants were confirmed as Phenacoccus solenopsis, Maconellicoccus hirsurtus, and Paracoccus marginatus based on their morphological characteristics and genes analysis such as 18S and 28S ribosomal, and COI mitochondrial genes. The percentage infestation of P. solenopsis was 40%, followed by P. marginatus (30%) and M. hirsurtus (15%) on Hibiscus rosa sinensis plants during specimen collection. Phenacoccus solenopsis was selected for further study based on the infestation level. It is one of the noxious sucking polyphagous pests causing severe losses and its control has been an issue of significance in pest management. Management of mealybug is challenging because of its wide host range, presence of a waxy coating on the body, and high reproductive potentiality. Fermented plant extracts (FPEs) and their wax degrading bacteria were screened for their relative toxicity against P. solenopsis. A total of 13 plant materials namely peppermint, Mexican mint, onion, garlic, turmeric, lemongrass, variegated mint, kaffir lime, lime, neem, galangal, mahogany, and ficus were selected for FPEs study based on their insecticidal properties. The FPEs of kaffir lime, turmeric, and ficus were effective in controlling P. solenopsis and scored the lowest LC50 value among the tested FPEs. All tested FPEs did not induce phytotoxicity to hibiscus leaves below 10% concentration (w/v) after 120 h postexposure, however, FPE of variegated mint and ficus had induced severe phytotoxic effect at >20% concentration to hibiscus leaves after 72 h post exposures. All FPEs were also evaluated for their repellency potential. Among the tested FPEs, fermented peppermint extract demonstrated the best repellent action against P. solenopsis after 1 h post exposure and it contained hydroxy-alpha-terpenyl acetate, 2-hydroxy methyl ester tetradecanoic acid, nonanol, and 2-heptanol attributed to repellent property while dropped after 24 h post exposure. The FPE of kaffir lime, turmeric, and ficus had less repellent action after 1 h and 3 h post exposure, however, fermented ficus extract could repel more than 50% P. solenopsis after 24 h post exposure. Based on repellent activity FPEs of pepper mint, Mexican mint, variegated mint, kaffir lime, galangal, lemongrass, and mahogany belonged to Class II (low repellent) after 24 h post exposure. FPEs of onion, turmeric, garlic and neem belonged to Class III (moderate repellent) and only fermented ficus extract belonged to Class IV (high repellent) after 24 h post exposure. On contrary, FPEs of pepper mint, Mexican mint, variegated mint, lemongrass, lime, and mahogany exhibited decreased repellent activity while FPEs of ficus, onion, turmeric, garlic, neem, kaffir lime, and galangal showed increasing repellent activity with exposure period. All the FPEs contained phenolic and alcoholic compounds in very trace amounts while butanoic acid was the highest abundant in the FPEs of ficus attributed to the highest repellent activity (Class IV) for P. solenopsis. Based on all the test results, fermented ficus extract was selected for waxdegrading bacteria screening. A total of 10 bacteria were isolated from the fermented ficus extract and confirmed by morphological and molecular characterization. Among the tested bacteria isolates, Klebsiella pneumoniae 0F1B1 was highly disruptive (83 % mortality) and inhibited the growth of P. solenopsis compared to other isolates. Bacillus sp. 42F1B3 exhibited the best mealybug wax degrading ability. In the glasshouse trial, fermented ficus extract performed the best in terms of the percentage reduction of P. solenopsis without any remarkable phytotoxicity on H. rosa sinensis, followed by kaffir lime and turmeric. It was noticed that H. cannabinas was more prone to phytotoxicity damage by FPEs than H. rosasinensis. Plant growth and photosynthesis were more inhibited in the FPE of turmeric-treated plants than the FPEs of kaffir lime and ficus-treated plants during the glasshouse trial, but all affected plants recovered after 15 days post treatment. The findings of the current study suggest the fermented kaffir lime extract may have beneficial effects on the growth of hibiscus plants along with mealybug control.In conclusion, FPE of ficus and Klebsiella pneumoniae 0F1B1 as wax degrading bacterium are good candidates to control P. solenopsis either as an insecticide or repellent. Different plants may have different responses to the phytotoxicity effect of FPEs. Therefore, the FPE of kaffir lime is suggested as a good candidate for the management of P. solenopsis in hibiscus plants.